2009
DOI: 10.1590/s1415-54192009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Movimentação dentária experimental em murinos: período de observação e plano dos cortes microscópicos

Abstract: ResumoObjetivo: este trabalho tem por finalidade explicitar aspectos microscópicos relevantes da movimentação dentária induzida em murinos quanto aos: (1) diferentes períodos de observação e (2) planos dos cortes microscópicos transversais e longitudinais. Os estudos experimentais sobre a movimentação dentária induzida em murinos variam quanto aos períodos e planos de cortes microscópicos, mesmo os trabalhos que utilizam especificamente o modelo de Heller e Nanda, de 1979. Para contribuir (1) na escolha do mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
0
12
0
8
Order By: Relevance
“…The DV root was chosen based on a previous study. 16 TRAP staining (TRAP 387 Kit, Sigma-Aldrich Chemicals, St Louis, Mo), a marker of osteoclasts, was used to evaluate alveolar bone resorption. 7,12,13,[17][18][19] The osteoclasts were multinucleated, TRAP-positive cells in contact with or near bone surfaces 12,13 and were evaluated in the periodontal ligament (PL) of the mesial face of the DV root of the maxillary right first molar.…”
Section: Tissue Responses To Corticotomy-and Corticision-assisted Toomentioning
confidence: 99%
“…The DV root was chosen based on a previous study. 16 TRAP staining (TRAP 387 Kit, Sigma-Aldrich Chemicals, St Louis, Mo), a marker of osteoclasts, was used to evaluate alveolar bone resorption. 7,12,13,[17][18][19] The osteoclasts were multinucleated, TRAP-positive cells in contact with or near bone surfaces 12,13 and were evaluated in the periodontal ligament (PL) of the mesial face of the DV root of the maxillary right first molar.…”
Section: Tissue Responses To Corticotomy-and Corticision-assisted Toomentioning
confidence: 99%
“…In 2009, Fracalossi et al 6 suggested a standardization of cross-sectional cuts of murine molars for the analysis of phenomena associated with induced tooth movement, and Santamaria Jr 22 described a practical way to quantify it. Still in 2009, Maldonado 19 investigated the effect of medications, particularly analgesic and anti-inflammatory drugs, on induced tooth movement and the frequency and severity of associated induced tooth movement.…”
Section: Palavras-chavementioning
confidence: 99%
“…Cães e macacos eram os animais de escolha nos estudos microscópicos da biologia do movimento dentário (Macapanpan et al, 1954). Com a evolução nos estudos experimentais, os ratos se firmaram como o modelo mais utilizado nos trabalhos que envolviam movimentação dentária experimental (Ren et al, 2004;Martins-Ortiz, 2004;Mavraganiet al, 2005;Santamaria et al, 2009;Fracalossi, 2009). Estes animais têm como vantagens menor custo de manutenção quando comparados aos dos primatas, gatos e cães, e a possibilidade de emprego em larga escala devido ao curto período de procriação e as ninhadas com vários filhotes (Ren et al, 2004).…”
Section: Remodelação óSseaunclassified
“…Quando esse dente sofre aplicação de uma força para mesial produz um movimento de inclinação (Martins-Ortiz, 2004;Santamaria et al, 2009;Fracalossi, 2009). …”
Section: Remodelação óSseaunclassified
See 1 more Smart Citation